Distributed key sharing based scheme for security clustering in unattended wireless sensor network - HONGHong Z; HANGQing-yang Z; IANLi-chao T; ANGLiang-min W (Tongxin xuebao)
For unattended wireless sensor network (UWSN),considering the collecting and efficiency and security prob-lems,a secure clustering scheme for UWSN was proposed,which implements a clustering algorithm with the secure au-thentication of mobile nodes.The clustering algorithm uses triangle's characteristic to improve connectivity,balances collect efficiency and power consumption.The distributed key sharing scheme is used to improve the security of the clustering algorithm,in which mobile node's public key is able to be searched with high efficiency in the distributed static nodes,and the signature of mobile nodes will be checked by using the searched public key.Simulation results show that the clustering algorithm is tend to triangular meshes when node density is increasing,and more than 95% attacks are tol-erated when compromised nodes are less than 20%.